Cardiovascular and Renal Implications of Myocardial Infarction in the ISCHEMIA-CKD Trial. (16th August 2022) - Chaitman, Bernard R.; Cyr, Derek D.; Alexander, Karen P.; Pracoń, Radosław; Bainey, Kevin R.; Mathew, Anoop; Acharya, Anjali; Kunichoff, Dennis F.; Fleg, Jerome L.; Lopes, Renato D.; Sidhu, Mandeep S.; Anthopolos, Rebecca; et al.
Abstract : Background: ISCHEMIA-CKD (International Study of Comparative Health Effectiveness With Medical and Invasive Approaches—Chronic Kidney Disease) reported an initial invasive treatment strategy did not reduce the risk of death or nonfatal myocardial infarction (MI) compared with a conservative treatment strategy in patients with advanced chronic kidney disease, stable coronary disease, and moderate or severe myocardial ischemia. The cumulative frequency of different MI type after randomization and subsequent prognosis have not been reported. Methods: MI classification was based on the Third Universal Definition for MI. For procedural MI, the primary MI definition used creatine kinase-MB as the preferred biomarker, whereas the secondary MI definition used cTn (cardiac troponin); both definitions included elevated biomarker-only events with higher thresholds than nonprocedural MIs. The cumulative frequency of MI type according to treatment strategy was determined. The association of MI with subsequent all-cause death and new dialysis initiation was assessed by treating MI as a time-dependent covariate. Results: The 3-year incidence of type 1 or 2 MI with the primary MI definition was 11.2% in invasive treatment strategy and 13.6% in conservative treatment strategy (hazard ratio [HR], 0.66 [95% CI, 0.42–1.02]). Procedural MIs were more frequent in invasive treatment strategy and accounted for 9.8% and 28.3% of all MIs with the primary and secondary MI definitions, respectively. Patients had an increased risk of all-cause death after type 1 MI (adjusted HR, 4.35 [95% CI, 2.73–6.93]) and after procedural MI with the primary (adjusted HR, 2.75 [95% CI, 0.99–7.60]) and secondary MI definitions (adjusted HR, 2.91 [95% CI, 1.73–4.88]). Dialysis initiation was increased after a type 1 MI (HR, 6.45 [95% CI, 2.59–16.08]) compared with patients without an MI. Conclusions: In ISCHEMIA-CKD, the invasive treatment strategy had higher rates of procedural MIs, particularly with the secondary MI definition, and lower rates of type 1 and 2 MIs. Procedural MIs, type 1 MIs, and type 2 MIs were associated with increased risk of subsequent death. Type 1 MI increased the risk of dialysis initiation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01985360.